Scritti (1910-1926). Vol. 2, Scritti 1917, a cura di Leonardo Rapone (in italiano) - Savant, Giovanna (International Gramsci Journal, 2023)
In this editorial presentation of Giovanna Savant’s review article and her detailed reconstruction of the historical context to Gramsci’s journalistic output in 1917, notes to page numbers where not otherwise specified are to the volume of the National Edition edited by Leonardo Rapone. Cross references are included to aid readers in finding articles included in the earlier publications of Gramsci’s pre-prison writings; the English-language version of her article also includes references to standard English translations, where available . It should be borne in mind that Gramsci’s various newspaper articles were at times heavily censored and a great merit of Rapone’s volume, apart from its more authoritative attribution of authorship, is to have often found the censored passages in archives or outlying areas where the censorship was less rigid and reinstated them. Readers should therefore realize that words quoted in the text of Savant’s contribution are not always to be found in the standard Italian collections of Gramsci’s writings, but sometimes only in the volume which she here discusses.